A look at the ethical requirements in face-to-face interaction from the perspective of Islamic teachings and psychological analysis - Ali Ahmad Panahi (اخلاق وحیانی)
Adherence to moral norms in social relations and especially in face-to-face interaction is one of the expectations that has been taken into consideration in different ways in Quranic and hadith teachings. The basic question is, what are the moral expectations in face-to-face interaction from the Islamic perspective, and what are the psychological effects of adhering to moral norms? In the upcoming research, the analysis and explanation of some ethical requirements of face-to-face interaction will be done with the descriptive-analytical processing method. By reflecting on Quranic and Hadith teachings and using psychological analysis, it can be claimed that in Islamic teachings, in order to improve and sustain social relations, and especially in face-to-face interaction, there are elements that are committed to. It has many benefits in improving social relations and especially in increasing the quality and quantity of face-to-face interaction. Adhering to these ethical elements in face-to-face interaction facilitates social relations, increases correct perception, increases social capital, increases empathy, promotes intimacy, develops peaceful coexistence, and increases mutual trust and reduces socio-cultural conflicts.